Regenerating Ipoh city mobility through high level of service (LOS) of public bus service - Bachok, Syahriah; Ponrohono, Zakiah; Mohamed Osman, Mariana; Ibrahim, Mansor (Elsevier, 2015)
Environmental setting in regeneration of Ipoh city mobility relates to how the public transport enhancements are undertaken. The history behind Ipoh city existence from mining-activities accessibility pattern creates a unique environment within the city. New technology, initiative and strategies targeted as creating sustainable transport system will increase the level of service (LOS) of public transport services. This research aims to evaluate the services of bus as a mode of accessing the destination such as residential, commercial and workplaces in Ipoh city. The data was collected through a series of on-board survey. The results on level of services of public bus in Ipoh shows that the regeneration initiatives and programmes in transportation system are vital and important factor in revitalize the dwindling city growth. It will increase the mobility within the city and encourage the economic and social activities.